PENERAPAN FUNGSI MANAJEMEN TERHADAP PENINGKATAN SUMBER DAYA MANUSIA DI KANTOR DESA LAGADING KECAMATAN PITU RIASE KABUPATEN SIDENRENG RAPPANG - Miranti Miranti; Lukman Lukman; Muhammad Ikbal (PRAJA: Jurnal Ilmiah Pemerintahan, 2021)
The purpose of this study is to determine the Implementation of Management Functions in the Lagading Village Office, Pitu Riase District, Sidenreng Rappang Regency, to determine the increase in human resources in the lagading village office, Pitu Riase sub-district, Sidenreng Rappang district and to determine the application of management functions to improving human resources in lagading village office, pitu riase sub-district, sidenreng rappang district. The population in this case was 1,291 people, while the sampling used was accidental sampling, using quantitative descriptive research, and data collection techniques were observation, questionnaires, and literature study. The data analysis technique used is descriptive statistics, data quality test, using frequency tables, regression methods and hypothesis testing. The results showed the application of the management function in the lagading village office, pitu riase sub-district, Sidenreng Rappang district with an average percentage value of 64.5% in the good category, while the increase in human resources in the lagading village office, pitu riase sub-district, Sidenreng Rappang district with an average percentage 65%. The application of the management function to improving human resources in the lagading village office, pitu riase sub-district, Sidenreng Rappang district has a significant effect of 19% and the remaining 81% is influenced by other variables that are not included in the conceptual framework of this study. This shows that the implementation of the management function to increase human resources in the lagading village office, Pitu Riase sub-district, Sidenreng Rappang district has not been optimal.Keywords: coordination and implementation of government.